Managing brands in Asia - Roll, Martin (Henry Stewart Talks, 2014)
The Asian strategy challenges, Strategic importance of branding, Three essentials of the brand-driven company, The chief marketing officer, The Asian brand no. 1 challenge, A new agenda for brands in Asia, Building a strong brand, Singapore airlines case study, Branding excellence, Touch point model for an airline company, Brands as financial assets, New business paradigm for globalizing Asian brands, Western brands in Asia